Power of Entrepreneurs [videorecording]. (In prosperity's wake : portraits of the post-war economy)
Gives a glimpse of the development of Japan"s post war econmy. It discusses the roles of entrepreneurs like Honda and Sony in the industrialization of Japan after the war.